FEATURES OF VOCABULARY EXERCISES CONTENTS IN FIRST GRADE SENIOR HIGH SCHOOL TEXTBOOK - Br Saragih, Thania Fransisca; Saragih, Erikson; Sianipar, Rutmelina (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
A Textbook is one of the tools used by a teacher to help them convey material to students during the learning process. The research used a qualitative study approach with an analytical research design of the contents of textbooks using the training method in the textbook. The objectives of the study are: (1) to see the contents of the Let's Learn English textbook to the 2013 curriculum was relevant. (2) To find out what kinds of new words are contact in the textbook. (3) Researching and analyzing how the practice of word forms in the textbook let's learn English. The results of this study show that content's of the Let's Learn English textbook for class X is very good. Researchers easily find information about vocabulary in the form of exercises. These findings show that: (1) Content textbooks is very relevant to the 2013 curriculum. (2) In analyzing the contents of textbooks, researchers find it easy to find information about new vocabulary. (3) The form of vocabulary exercises according to the material from the content Based on the researcher about the analysis of this textbook, the suggestion is that the reader does not just read the material in the text, but understands the meaning and purpose of the material so that information would received accurately.